2020
DOI: 10.2169/internalmedicine.4554-20
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Gastroenteritis in an Ulcerative Colitis Patient During Treatment with Tumor Necrosis Factor-alpha Antagonist

Abstract: A 45-year-old man with steroid-dependent ulcerative pancolitis was hospitalized with frequent diarrhea, abdominal pain and distension 3 months after induction of golimumab, a tumor necrosis factor-alpha antagonist. Computed tomography showed wall thickening from the stomach to the colon and massive ascites. Peripheral blood test revealed eosinophilia. A large number of eosinophils were observed in the ascites fluid. Although esophagogastroduodenoscopy showed no abnormal findings and colonoscopy showed ulcerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Benralizumab is known to directly eliminate eosinophils by inducing apoptosis by directly binding to IL-5 receptor α on the surface of eosinophils and inducing natural killer (NK) cells by antibody-dependent cellular cytotoxicity [9] . It was also reported that administration of steroids in patients with anti-tumor necrosis factor alpha (TNFα) antibody-resistant UC combined with eosinophilic gastroenteritis resulted in prominent improvement in eosinophilic in ltration and improvement in UC activity [10] . However, in cases where in ammation is prolonged despite maintenance treatment for UC, such as biologics, the relationship between the degree of eosinophilic in ltration as a histological nding in the colonic mucosa and the disease state has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Benralizumab is known to directly eliminate eosinophils by inducing apoptosis by directly binding to IL-5 receptor α on the surface of eosinophils and inducing natural killer (NK) cells by antibody-dependent cellular cytotoxicity [9] . It was also reported that administration of steroids in patients with anti-tumor necrosis factor alpha (TNFα) antibody-resistant UC combined with eosinophilic gastroenteritis resulted in prominent improvement in eosinophilic in ltration and improvement in UC activity [10] . However, in cases where in ammation is prolonged despite maintenance treatment for UC, such as biologics, the relationship between the degree of eosinophilic in ltration as a histological nding in the colonic mucosa and the disease state has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] It was also reported that administration of steroids in patients with anti-tumor necrosis factor alpha (TNFα) antibody-resistant UC combined with eosinophilic gastroenteritis resulted in prominent improvement in eosinophilic infiltration and improvement in UC activity. [ 10 ] However, in cases where inflammation is prolonged despite maintenance treatment for UC, such as biologics, the relationship between the degree of eosinophilic infiltration as a histological finding in the colonic mucosa and the disease state has not been thoroughly investigated. In addition, the role of removal of eosinophils by short-term steroid administration in the pathophysiology of refractory UC is not elucidated.…”
Section: Introductionmentioning
confidence: 99%